Effectiveness of Online Learning Assisted by Olabs Virtual Laboratorium in Improving Students' Science Process Skills (International Journal of Active Learning, 2022)
Most learners are less able to understand lessons in distance learning, so it is very necessary for teacher guidance to follow learning through observation, experimenting, and active experiments. The purpose of this study is to analyze the effectiveness of online learning assisted by virtual laboratories in improving the science process skills of SMKN Jateng di Semarang students. The research method uses the pretest-postest control group design with analysis of N-gain parametric statistical test data, as well as the t-test sample paired test. Samples in this study were obtained by purposive random sampling techniques from class X SMK N Jateng di Semarang which amounted to 120 students. The results of the analysis of the skills of the experimental grade acid-based material science process obtained an average pretest result of 57.2 and an average post-test result of 69.6 so it has a value of g = 0.43 with a medium category. In the control class analysis, the pretest average result was 47.4 and the average post-test result was 54.36 so it had a value of g = 0.27 with a low category. The results of the T-test in the experimental class were obtained that there was a significant influence with a sig. 0.000 0.05 so Ho was rejected and Ha was accepted, so there was a difference in the average skill of the science process before and after learning. online assisted virtual laboratories olabs.